Patih Keren (Health Training Program Reproduction Of Children With Disabilities) To Improving Children's Reproductive Health At Slb Surakarta - Heni Purwaningsih; Yuli Widyastuti; Nurul Istiqomah (Peneliti Teknologi Teknik Indonesia, 2023)
The increase in incidents of sexual violence against children with disabilities, which occurs from year to year, is caused by their disabilities and limited intelligence, making them more vulnerable to sexual abuse and violence. According to data from the Ministry of Women's Empowerment and Child Protection (KPPPA) in 2021, there was an increase in the rate of violence and sexual harassment against children with disabilities by 48% compared to the previous year. Previous research has also identified various reproductive health problems faced by children with disabilities, including anxiety, sexual abuse, pregnancy in teenage girls, and diseases resulting from promiscuous sexual behavior. Limited access to special schools, a lack of available educators, as well as a lack of educational facilities, infrastructure and media, means that not all children with disabilities receive appropriate education. Therefore, it is important for children with disabilities in special schools, special middle schools and special high schools to understand well the aspects of their reproductive health. Accurate and precise information about reproductive health is very important for children with disabilities. The aim of this community service activity is to improve the knowledge, attitudes and behavior of children with disabilities through reproductive health education training, making learning media about reproductive health, and making reproductive health books specifically for children with disabilities. Outputs include increasing knowledge, attitudes and behavior of children with disabilities related to reproductive health, simple but effective reproductive health learning media, reproductive health books with ISBN numbers, publication of scientific articles, as well as community service activities and video documentation of these activities.